2003
DOI: 10.1038/sj.onc.1206798
|View full text |Cite
|
Sign up to set email alerts
|

The phosphotyrosine phosphatase SHP2 is a critical mediator of transformation induced by the oncogenic fibroblast growth factor receptor 3

Abstract: Receptor tyrosine kinases (RTKs) such as the fibroblast growth factor receptor (FGFR) and the epidermal growth factor receptor are overexpressed in a variety of cancers. In addition to overexpression, the FGFRs are found mutated in some cancers. The Src homology 2 domaincontaining phosphotyrosine phosphatase (SHP2) is a critical mediator of RTK signaling, but its role in oncogenic RTK-induced cell transformation and cancer development is largely unknown. In the current report, we demonstrate that constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 54 publications
(67 reference statements)
8
72
0
Order By: Relevance
“…We have recently demonstrated that SHP2 mediates the transformation of NIH-3T3 cells by K/E-FR3 via positively modulating the Ras-ERK and PI3K-Akt signaling pathways (Agazie et al, 2003). We have further shown that a phosphotyrosyl protein of B100 KDa (p100) coprecipitates with K/E-FR3 in cells expressing R/E-SHP2 suggesting that this protein could be a potential SHP2 substrate (Agazie et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently demonstrated that SHP2 mediates the transformation of NIH-3T3 cells by K/E-FR3 via positively modulating the Ras-ERK and PI3K-Akt signaling pathways (Agazie et al, 2003). We have further shown that a phosphotyrosyl protein of B100 KDa (p100) coprecipitates with K/E-FR3 in cells expressing R/E-SHP2 suggesting that this protein could be a potential SHP2 substrate (Agazie et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, SHP2 has been shown to be required for cell transformation induced by v-Src (Hakak et al, 2000). More recently, we have demonstrated that SHP2 is essential for cell transformation induced by the constitutively active FGFR3 (K650E-FGFR3), hereinafter referred to as K/E-FR3 (Agazie et al, 2003). Expression of dominant-negative SHP2 (R465E-SHP2), hereinafter referred to as R/E-SHP2, reverses cell transformation as evidenced by morphological changes, inability to form foci in culture and reduced growth rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12,30 Second, SHP2 promotes cell transformation induced by v-Src and the constitutively active form of FGFR3. [1][2][3] and associated leukemia. 4 And finally, the SHP2 protein is overexpressed in approximately 70% of infiltrating ductal carcinoma of the human breast.…”
Section: Discussionmentioning
confidence: 99%
“…First, SHP2 is essential for cell transformation induced by v-Src 1 and the constitutively active form of fibroblast growth factor receptor 3 (K650E-FGFR3). 2,3 And second, SHP2 has been implicated in the development of Noonan syndrome and associated leukemia. 4 This was based on the discovery of activating SHP2 mutations, sometimes referred to as leukemogenic SHP2 mutants, in patients with these diseases.…”
mentioning
confidence: 99%